Comparison of Posteromedial Versus Posterolateral Approach for Posterior Malleolus Fixation in Trimalleolar Ankle Fractures. Issue 1 (February 2017) - Zhong, Sheng; Shen, Lin; Zhao, Jia‐guo; Chen, Jie; Xie, Jin‐feng; Shi, Qi; Wu, Ying‐hua; Zeng, Xian‐tie
Abstract : Objective: To compare clinical and radiographic outcomes of posterior malleolar fractures (PMF) treated with lag screws from anterior to posterior versus posterior to anterior approach. Methods: We retrospectively analyzed 48 patients with trimalleolar fractures who underwent open reduction and internal fixation (ORIF) with either posteromedial (PM) or posterolateral (PL) approaches between January 2012 and December 2014. Fixation of the posterior malleolus was made with anteroposterior screws in 20 patients using the PM approach and posteroanterior screws in 28 patients using the PL approach. The American Orthopedic Foot and Ankle Society (AOFAS) scores and range of motion (ROM) of the ankle were used as the main outcome measurements, and results were evaluated at the 6‐month, 12‐month and final follow‐up. Postoperative radiographs and computed tomography scans were used to evaluate the residual gap/step‐off. The degree of arthritis was evaluated on final follow‐up using Bargon criteria. Other complications were also recorded to compare the clinical outcomes of the two approaches. Result: The mean duration of follow‐up regardless of the approaches was 21.1 months (range, 15–54 months). None of the patients developed delayed union or nonunion. Functional bone healing was obtained in all patients at 10.7 weeks (range, 8–16 weeks). The mean AOFAS scores of the PM group at the postoperative 6‐mouth, 12‐month, and final follow‐up were 91.4 (range, 82–100), 92.5 (range, 84–100), and 92.9 (range, 86–100), respectively. In the PL group, the mean AOFAS scores were 89.9 (range, 72–100), 91.4 (range, 77–100), and 91.9 (range, 77–100), respectively. At the final follow‐up, the median loss of range of motion (ROM) for dorsiflexion and plantaflexion were 0°(0°, 5°) and 0°(0°, 0°), respectively, in both groups. There were no significant differences between the two approaches in AOFAS scores and ROM of the ankle in each period postoperatively ( P > 0.05). Two patients in the PL group and 1 in the PM group developed Bargon grade 2 or 3 arthritis. We detected a 2‐mm and 3‐mm step‐off in 1 patient in the PM and PL groups, respectively. Conclusion: Satisfactory results were obtained by using the two approaches for fixation of posterior malleolus, and the approaches have similar clinical and radiographic outcomes. Surgeons should choose the appropriate approach based on their experience.